The marine metabolite heptylprodigiosin bioactivity and apoptotic mechanism of action in leukemic and other cancer cells - Ranches, Glory D.; Concepcion, Gisela P. (Quezon City Marine Science Institute, College of Science, University of the Philippines Diliman, 2008)
Heptylprodigiosin (HPDG) is a marine microbial metabolite produced by a bacterium isolated from a Philippine tunicate. A tripyrrole ring and a heptyl substituent typify HPDG as an analog of the prodigiosins. A wide spectrum of bioactivities possessed by HPDG, such as antimalarial, antimicrobial, immunosuppressant and proapoptotic, substantiate that this red metabolite is a potential therapeutic drug for infectious and non-infectious diseases.
Thesis (M.S. Marine Science major in Marine Biotechnology)--University of the Philippines Diliman
Keywords: Tunicata -- Philippines; Antimalarials -- Philippines